Two-phase mixture model for substrate degradation and photo-hydrogen production in an entrapped-cell photobioreactor under various light intensities. Issue 22 (6th February 2015) - Guo, Cheng-Long; Cao, Hong-Xia; Pei, Hong-Shan; Guo, Fei-Qiang; Liu, Da-Meng
Abstract : Substrate degradation and photo-hydrogen production under various light intensities was predicted using the developed two-phase mixture model. Abstract : A two-phase mixture model was developed for revealing the interaction between substrate degradation and photo-hydrogen production in an entrapped-cell photobioreactor under various light intensities. The effects of the porosity of the packed bed and the height of the photobioreactor on the substrate degradation rate (SDR) and hydrogen production rate (HPR) were also predicted at different light intensities.